2018
DOI: 10.1007/s11325-018-1695-6
|View full text |Cite
|
Sign up to set email alerts
|

Noncontact identification of sleep-disturbed breathing from smartphone-recorded sounds validated by polysomnography

Abstract: NCT03288376; clinicaltrials.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Smartphones feature various apps [ 25 ]. Internal sensors and external (connectable) devices measure blood oxygen, pulse, body movement (using accelerometers or sonars), and breath sounds during sleep [ 12 ]. Studies using oximeter/accelerometer combinations to diagnose sleep apnea found that body position data aided in respiratory movement assessment [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smartphones feature various apps [ 25 ]. Internal sensors and external (connectable) devices measure blood oxygen, pulse, body movement (using accelerometers or sonars), and breath sounds during sleep [ 12 ]. Studies using oximeter/accelerometer combinations to diagnose sleep apnea found that body position data aided in respiratory movement assessment [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Snoring differs between healthy people and sleep apnea patients; the noises alone accurately separate the groups [ 28 ]. In addition, various recent apps feature algorithms analyzing oxygen saturation, body position during sleep, and sleep breathing sounds [ 5 10 , 12 , 14 , 15 , 29 ]. Furthermore, because smartphones use motion, sound, oximetry, and combinations thereof to detect abnormal sleep, we evaluated the effects of the various methods on diagnostic accuracy; we performed subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A less accurate, but very low–burden, detection method is to use smartphone screen interaction to approximate bedtimes and waking times 157 . Smartphones have also shown promise for the evaluation of perceived sleep quality using patient reports as well as detection of sleep‐disordered breathing using built‐in microphones 158‐161 . In addition, the MyHeart Counts study from Apple uses smartphones to detect ambient light 162 .…”
Section: Digital Phenotyping: Mobile Technology To Collect Pghdmentioning
confidence: 99%
“…Narayan et al demonstrated that it is possible to detect disturbed and normal breathing patterns from ambient sounds recorded by an unmodified smartphone microphone . The authors studied 91 patients undergoing polysomnography by using a Samsung Galaxy S5 smartphone placed less than 1 m from the head of the bed to record ambient sounds.…”
Section: Four System Architectures Of Biosensors For Personal Mhealthmentioning
confidence: 99%